Pemikiran Tuan Minal dalam Membahaskan Aspek Mabadi ‘Ilm Tawhid dan Ilah dalam Kitab `Aqidah al-Najin: Tuan Minal’s Thinking in Debating Aspen’s Mabadi ‘Ilm Tawhid and Ilah in `Aqidah al-Najin Book - yusoff, pauzi; Hamat, Mohd Fauzi; Mohamed Adnan, Mohamad Azrien (Jurnal Usuluddin, 2022)
One of Nusantara’s experts, Tuan Minal, is adamant on publishing works, particularly in the area of religion. The `Aqidah al-Najin fi `Ilm Usul al-Din, his book, is still in use today. This article will briefly explain the book `Aqidah al-Najin, which also discuss the peculiarities of this book in terms of definition, Mabadi `Ilm Tawhid and ilah. This study uses a qualitative method where the book `Aqidah al-Najin is used as a primary source, while the process of analyzing the data is to use the method of content analysis of the book by making a comparative analysis of the work with several other scholars of the archipelago. The paper summarizes that Tuan Minal attaches great importance to the aspect of accuracy by choosing the right and appropriate words to make a definition. In addition, Tuan Minal tried to compile ten Mabadi ’Ilm Tawhid in learning the science of tawhid well and organized and carefully in discussing matters related to the divine spirit.